Analysis of cases with primary retroperitoneal tumors - Çalışkan, Müjgan; Evren, İsmail; Acar, Aylin; Ekşi, Mithat (Yerküre Tanıtım & Yayıncılık Hizmetleri A S, 2019)
Objective: Retroperitoneal tumors are rare and most of them arise from mesodermal or neuroectodermal tissues and residues of the embryonic urogenital body. Retroperitoneal malignant tumors are seen more often than benign lesions. Due to their anatomic location and slow growth, pain and neurological symptoms do not appear until later stages. In this article, we aim to present our experience in eight cases with primary retroperitoneal tumor. Methods: Eight patients who underwent retroperitoneal tumor excision between April 2009 and April 2016 were included in the study. Gender, age, patients' complaints, the location, type and size of the tumor, surgical techniques, and morbidity, recurrence, and mortality rates were evaluated. The mean follow-up period was 41.3 months. Results: Four of the eight patients were females and the mean age was 48.6 years. The retroperitoneal mass was located in the abdomen (n= 4) and in the pelvis (n= 4). In addition to abdominal pain, some patients experienced back and leg pain, difficult urination, and constipation. Intra-operative biopsy was performed previously during a laparotomy (n= 2). Mass excision was performed by open and laparoscopic surgery. Variable histopathological diagnoses were determined, such as schwannoma, cystic mesothelioma, angiomyolipoma, epidermoid cyst, liposarcoma, ganglioneuroma, and neurofibroma. Morbidity included intra-operative bleeding (n= 1), post-operative deep vein thrombosis (n= 2), and pulmonary embolism (n= 1). Postoperatively there were neither recurrences nor mortality. Conclusion: Primary retroperitoneal tumors can be located in different regions, but we did not find any tumors localized in the left lumbar region. The pathological diagnoses were heterogeneous, including seven benign lesions and one malignant lesion.

Amaç: Retroperitoneal tümörler nadirdir ve çoğu mezodermal veya nöroektodermal kökenli olup ve embriyonik ürogenital cismin kalıntılarından kaynaklanmaktadır. Retroperitoneal malign tümörler benign lezyonlardan daha sık görülür. Anatomik yerleşimleri ve yavaş büyümeleri nedeniyle, ağrı ve nörolojik semptomlar gecikmiş aşamalara kadar görülmez. Bu yazıda primer retroperitoneal tümörlü sekiz olguluk deneyimimizi sunmayı amaçladık. Yöntemler: Nisan 2009-Nisan 2016 tarihleri arasında retroperitoneal tümör eksizyonu yapılan sekiz hasta çalışmaya dahil edildi. Cinsiyet, yaş, hastanın şikayetleri, yeri, tümör tipi ve boyutu, cerrahi teknikler, morbidite, nüks ve mortalite oranları değerlendirildi. Ortalama izlem süresi 41,3 ay idi. Bulgular: Sekiz hastadan dördü kadın, yaş ortalaması 48.6 idi. Retroperitoneal kitlelerin 4’ü batın (n=4) ve 4’ü pelvis (n=4) yerleşimliydi. Karın ağrısına ek olarak, bazı hastalarda sırt ve bacak ağrısı, zor idrara çıkma ve kabızlık şikayetleri tespit edilmiştir. Laparotomi öncesi intraoperatif biyopsi 2 hastada uygulandı. (n=2). Kitle eksizyonu açık ve laparoskopik cerrahi ile yapıldı. Schwannoma, kistik mezotelyoma, anjiomyolipom, epidermoid kist, liposarkom, ganglionöroma ve nörofibrom gibi değişken histopatolojik tanılar belirlendi. Hastaların dördünde intraoperatif (kanama (n=1), ameliyat sonrası derin ven trombozu (n=2) ve pulmoner emboli (n=1)) morbidite izlendi. Postoperatif dönemde rekürrens ya da mortalite izlenmedi. Sonuç: Primer retroperitoneal tümörler farklı bölgelerde yerleşebilmekle birlikte sol lumbar bölgede herhangi bir tümör lokalizasyonu izlenmedi. Yedi benign lezyon ve bir malign lezyon da dahil olmak üzere patolojik tanı heterojen olarak belirlendi.
Primer retroperitoneal tümörlü olguların analizi
WOS: 000464102400007
Keywords: Mesenchymal Tissues; Retroperitoneum; Tumor; Mezenkimal Dokular; Retroperiton; Tümör